ESTUDIO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA EMPRESA PROCESADORA Y COMERCIALIZADORA DE SALSA DE TOMATE EN LA CIUDAD DE CATAMAYO, CANTÓN CATAMAYO, PROVINCIA DE LOJA - MAZA ROBLES, LUIS FERNANDO (2019)
The objective of this research work was to determine the financial feasibility of the project entitled "Feasibility study for the creation of a processing and marketing company of tomato sauce in the city of Catamayo". To this end, the methodology was established by using deductive, inductive, quantitative, descriptive and analytical methods and data collection techniques such as survey, interview and direct observation. Supported of the previous techniques the study was made market to know the demand of the product, for it first settled down the sample using data of INEC 2010 and projecting them to the 2018 with the rate of growth of the 1.4% being 6,554 families to who it was applied 363 surveys and of the GAD of Catamayo where they exist registered 83 establishments of food to which a census was made, determining itself a total demand insatisfecha of 33.945.470 grams of sauce of tomato for the first year. The technical study was elaborated, where the capacity of production of 24.960.000 grams to the year that will grow in a 5,0% annually to increase the participation in the market, in addition within the study settled down was arranged to locate to the company within the city, specifically in the urban parish of San Jose. Also the organizational structure and legal for the company was defined, which constituted under the name of Romanesa Cia Ltda., to that designed the structural organizational chart to him, functional positional and the manuals of functions for the four jobs. In the economic study the initial investment in fixed assets, deferred and circulating was detailed whose amount is of $ 27.172,25 that is detailed in the budgets. The total cost of production calculated that ascends to $ 67.442,68 and income of $ 80.149,01 in the first year, which allowed to define the sale price of $ 0.90 for sachet of 200gr and $ 3.25 for the gallon of 4000gr, having a margin of initial utility of 20% and 8%. Also it was 5 elaborated the earnings statement and the point of balance which indicates that the company must work to 79,08% of the installed capacity and must have sales by the value of $ 63.824,20 not to have losses nor gains. Finally evaluation elaborated financial where feasibility determined of project, because the main indicators were positive as the Net Present Value (VAN) that threw a value of $ 30.886,79 whereas the Internal Rate of Retorno (TIR) was located in greater 45,24% to the cost of the money in the market, the Relation benefit cost (RBC) I turn out to be from $0.33 by each invested dollar, the Period of Recovery of Capital (PRC) calculated to the 2 years and 9 months and 25 days, and the Analysis of Sensitivity (AS) indicates that it will be possible to be worked until with an increase in the costs of 12,25% and one diminution of the income of 10,88%.